BUDAYA POLITIK PARTAI DI TINGKAT LOKAL: PARTAI KEADILAN SEJAHTERA DI PURBALINGGA - Indaru Setyo Nurprojo; Bowo Sugiarto (Jurnal Ilmu Politik dan Pemerintahan, 2011)
This article is to describe the political culture of the Prosperous Justice Party (PKS) in Purbalingga. Political culture in this article are understood as the number of values, knowledge and fundamental beliefs that give shape and substance to the political processes. This article will also discuss the political socialization experienced by PKS cadres to gain a good understanding of the political culture of PKS. The approach used in this article are therefore more focused to institutional analysis approach of the processes that institutionalized. Values and beliefs that form the basis of political culture from the PKS their understanding of Islam. Islam as a religion is believed its teachings to include all areas of life, including politics. Political activity is believed to be part of the missionary activity. Political socialization experienced by the PKS cadres, mainly obtained through halaqah.